Oncological and functional outcomes of open versus laparoscopic partial nephrectomy in T1b tumors: A single-center analysis - Kartal, Ibrahim (Int Braz J Urol, 2020)
PURPOSE: This study aims to evaluate the oncological and functional results of open partial nephrectomy (OPN) and laparoscopic partial nephrectomy (LPN) at the T1b clinical stage, which constitutes 25% of renal cell carcinomas (RCC) at diagnosis. MATERIALS AND METHODS: The characteristics of 63 patients with stage T1b solitary tumor who underwent OPN (41) or LPN (22) were compared. The survival analysis was performed using the Kaplan-Meier method. Univariate and multivariate Cox regression analyses were performed to determine the factors affecting disease-free survival. Potential predictive factors, which might affect the postoperative glomerular filtration rate (GFR), were evaluated using multivariate linear regression analysis. RESULTS: No differences were observed between OPN and LPN groups regarding patient and tumor characteristics. Although the warm ischemia time, intraoperative estimated blood loss, and operation duration were higher in the LPN group, no differences were noted between the two techniques regarding complication rates (p<0.001, p=0.023, p≤0.001, and p=0.190, respectively). The median hospitalization time was shorter in the LPN group than that in the OPN group (4 and 5 days, respectively), with less severe complications. No intergroup differences were observed regarding cancer-specific survival (CSS), disease-free survival (DFS), and overall survival (OS). The evaluation of the factors affecting DFS showed that age was an effective parameter (RR = 1.112, 95% CI: 1.010–8.254), but the surgical technique was not. CONCLUSION: No differences were observed between OPN and LPN techniques between oncological and functional outcomes in patients with clinical stage T1b RCC.